The Effect of Epimedium Extract on the Pharmacokinetics of Tadalafil in Beagle Dogs - Fan, Lingling; Li, Pengzhe; Song, Xuhao; Liao, Huobing; Zhai, Luxin; Qiu, Xiangjun (International Journal of Public Health and Medical Research, 2024)
Objective: A sensitive high performance liquid chromatography with diode array detector (HPLC-DAD) method for determination of tadalafil in beagle dog plasma was developed, and to investigate the effect of Epimedium extract on the pharmacokinetics of tadalafil in beagle dogs. Methods: The beagle dog plasma was extracted with ethyl acetate under alkaline conditions. Tadalafil and internal standard (IS, carbamazepine) were separated on an XDB-C18 column, acetonitrile and 0.1% trifluoroacetic acid were used as the mobile phase. Tadalafil and IS were detected by DAD. This experiment adopts the experimental design of double cycle self-control. In the first cycle (group A), six beagle dogs were given Tadalafil 1 mg/kg orally in a single dose. In the second period (Group B), the same six beagle dogs were orally given Epimedium extract 0.6 g/kg once a day for 7 consecutive days, then Tadalafil was orally given. At the different time points after tadalafil was given in the two periods, the blood samples were collected. The concentration of tadalafil were detected by the developed HPLC method. DAS 2.0 was used to calculate the pharmacokinetic parameters of tadalafil. Results: Under the current experimental conditions, this HPLC-UV method showed good linearity in the detection of tadalafil. Inter-day and intra-day precision did not exceed 10%, the range of accuracy values were from -6.40% to 8.12%. The results of extraction recovery, and stability were met the requirements of FDA approval guidelines of bioanalytical method validation. Compared with the control group, the Cmax of the experimental group decreased by 42.91%, the experimental group showed a significant increase in CLz/F, the AUC(0-t) and AUC (0-∞) of tadalafil in the experimental group decreased by 24.60% and 29.57%, respectively. Conclusions: In this study, a HPLC-UV method for the determination of plasma tadalafil concentration was established. Epimedium extract could induce metabolism of tadalafil in beagle dogs and reduce plasma exposure to tadalafil.